Answer:
x = 25√2, y = 25
Step-by-step explanation:
x = 25(√2) = 25√2
y = 25
Answer:
Expand it.
(1+2i)^3 is equal to (1+2i)(1+2i)(1+2i).
Multiply everything out (being sure to multiply <em>every</em> term. (1+2i) * (1+2i) = 1+2i+2i+4i^2.
i is the square root of negative one, so i^2 is just -1. 1+2i+2i-4 is what you get from the first two, so now simplify that:
1-4 + 2i+2i = (-3+4i) and now multiply that by (1+2i):
(-3+4i) * (1+2i) = -3 - 6i +4i +8i^2.
Simplify again, and the answer is: -11-2i
Step-by-step explanation:
I hope this helps - really my only tip is don't spend time thinking about what i is, that just hurts your brain. Just remember that i^2 is equal to negative one, and treat it like regular multiplication and you will be fine.
Answer:
y=sqrt((x+a)/-2b))
F=(5/9)C+32
Can't read the rest
Step-by-step explanation:
-2by^2=x+a
y^2=(x+a)/-2b
y=sqrt((x+a)/-2b))
F-32=(5/9)C
F=(5/9)C+32 (The actual Fahrenheit-Celcius formula)
NOTE: The other pictures cannot be opened.
100 because of complementary angles
Answer:
2
Step-by-step explanation:
2x is the slope which is just 2